2015
DOI: 10.1117/1.jbo.20.3.036017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnose human colonic tissues by terahertz near-field imaging

Abstract: Abstract. Based on a terahertz (THz) pipe-based near-field imaging system, we demonstrate the capability of THz imaging to diagnose freshly surgically excised human colonic tissues. Through THz near-field scanning the absorbance of the colonic tissues, the acquired images can clearly distinguish cancerous tissues from healthy tissues fast and automatically without pathological hematoxylin and eosin stain diagnosis. A statistical study on 58 specimens (20 healthy tissues and 38 tissues with tumor) from 31 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Taking pathological biopsy as the gold standard for reference, THz in vitro imaging has been extensively applied in digestive system [54][55][56][57][58][59][60][61][62][63][64], integumentary system [65,66], reproductive system [67][68][69][70], respiratory system [57], and nervous system [49] neoplasms. Frozen sections [54,56], formalin fixations [57], and paraffin sections [67] have typically been applied as specimen pretreatment processes to overcome the strong water absorption loss.…”
Section: Current Status Of Thz Imaging Studiesmentioning
confidence: 99%
“…Taking pathological biopsy as the gold standard for reference, THz in vitro imaging has been extensively applied in digestive system [54][55][56][57][58][59][60][61][62][63][64], integumentary system [65,66], reproductive system [67][68][69][70], respiratory system [57], and nervous system [49] neoplasms. Frozen sections [54,56], formalin fixations [57], and paraffin sections [67] have typically been applied as specimen pretreatment processes to overcome the strong water absorption loss.…”
Section: Current Status Of Thz Imaging Studiesmentioning
confidence: 99%
“…Most single frequency systems used for imaging colon tissue thus far work at around 0.6 THz (500 µm) as a compromise between these two factors. A notable exception is the work done by Chen et al[ 41 ] in transmission imaging at 0.3 THz (approximately 1 mm); they compensate for the lower far-field resolution by using a specially designed aperture which allows for significantly higher resolution in the near field.…”
Section: Overview Of Experimental Workmentioning
confidence: 99%
“…Two groups so far have demonstrated waveguide based THz imaging. Chen et al[ 41 ] used a polymethyl-methacrylate waveguide to demonstrate THz transmission imaging of human colon tissue and Doradla et al[ 37 ] demonstrated reflection modality imaging using a single channel THz waveguide.…”
Section: Overview Of Experimental Workmentioning
confidence: 99%
“…17 In contrast, the continuous-THz-wave imaging system, which has also been widely employed for biomedical imaging of various tissues, is simple, low cost, and stable. [19][20][21][22] Also, the imaging speed of the continuous-THz-wave imaging system is always faster than the pulsed imaging system without the need for coherent detection of THz pulses. In addition, the absorption of water vapor at low THz frequencies is small 17 and thus the continuous-THz-wave imaging system could be more feasible for practical applications.…”
Section: Introductionmentioning
confidence: 99%